Effective use of the Orticochea Flap in the Surgical Treatment of Non-Hodgkin Lymphoma : Case Report - Anastasia Harsono; Metaudina Pratiwi; Dominic Tjokrovonco (Perkumpulan Kedokteran Militer, 2025)
Background: Head and neck non-Hodgkin lymphoma may clinically and radiologically mimic inflammatory disease, sarcoma, or other malignant tumors, creating diagnostic and reconstructive challenges. Large occipital scalp defects require vascularized, hair-bearing tissue coverage. This case series aims to describe the role of the Orticochea flap for reconstruction of large occipital scalp defects after tumor excision, with emphasis on diagnostic uncertainty, operative management, and postoperative wound outcome. Case illustration: The complete available case involved a 55-year-old immunocompetent woman with a rapidly enlarging painless mass extending from the posterior neck to the occipital scalp over four months, accompanied by an axillary lump. Magnetic resonance imaging suggested a soft tissue malignancy, initially considered liposarcoma. Wide excision with a 5-mm margin produced a 20 x 20 cm scalp defect, reconstructed using an Orticochea flap. Histopathology suggested non-Hodgkin lymphoma, although the final immunohistochemical subtype requires completion by the authors. Additional cases should be inserted before final submission. Discussion: The Orticochea flap provides broad local scalp advancement while preserving vascularity and hair-bearing coverage. In the available case, early wound healing was satisfactory, but delayed occipital wound dehiscence occurred and was managed conservatively with daily pure honey dressing during chemotherapy. Conclusion: The Orticochea flap may be useful for large occipital scalp defects requiring local hair-bearing coverage, but complete oncologic diagnosis, additional cases, and longer follow-up are needed before final case-series submission.